Root biomass and organic reserves of coastcross intercropping or not with “Arachis pintoi”, with or without nitrogen, under grazing Biomassa radicular e reservas orgânicas em coastcross consorciada ou não com "Arachis pintoi", com e sem nitrogênio, sob pastejo - Clóves Cabreira Jobim; Juliana Cantos Faveri; Augusto Manoel Rodrigues; Ulysses Cecato; Ossival Lolato Ribeiro; Simony Marta Bernardo Lugão (Revista Brasileira de Saúde e Produção Animal, 2011)
The aim of this study was to evaluate the non-structural carbohydrates and root biomass in pastures of Coastcross + Arachis pintoi; Coastcross + Arachis pintoi with 100kg/ha of nitrogen (N); Coastcross + Arachis pintoi with 200kg/ha of N; and Coastcross with 200kg/ha of N, in the seasons of winter, spring, summer and autumn. In the experimental was used a complete randomized block design with subdivided parcels, with two repetitions (blocks) was used. The use of nitrogen fertilization (100kg/ha) associated to the Arachis pintoi provided the highest content of non-structural carbohydrates (0,3942g/hg) in the roots and greater root biomass (0,4483kg/m3). The content of non-structural carbohydrates and the root biomass were higher in the summer and autumn. The concentration of 63%, 24 % and 13% of the root biomass occurred in the layer of 0 - 15; 15 - 30 and 30 - 45cm of the ground, however, it did not have difference in the root biomass between the treatments with or without intercropping, in the studied depths. The concentrations of the non-structural carbohydrates were similar in the different depths of the root. Objetivou-se neste trabalho avaliar a concentração de carboidrato não-estrutural e biomassa radicular em pastagens de grama Coastcross + Arachis pintoi; Coastcross + Arachis pintoi com 100kg/ha de nitrogênio (N); Coastcross + Arachis pintoi com 200kg/ha de N; e Coastcross com 200kg/ha de N, nos períodos de verão, outono e inverno. Utilizou-se delineamento experimental em blocos ao acaso com os tratamentos em esquema de parcelas subdivididas, com duas repetições (blocos). A utilização de adubação nitrogenada (100kg/ha) associada ao Arachis pintoi proporcionou maior concentração de carboidrato não estrutural (0,3942g/hg) na raiz e maior biomassa radicular (0,4483kg/m3). A concentração de carboidrato não estrutural e a biomassa radicular foram elevadas no verão e outono. A concentração de biomassa radicular foi de 63%, 24% e 13% nas profundidades de 0 - 15, 15 - 30 e 30 - 45cm, entretanto, não houve diferença na biomassa radicular entre os tratamentos com e sem consorciação, nas profundidades estudadas. As concentrações de carboidratos não estruturais foram semelhantes nas diferentes profundidades das raízes.